Racial, socioeconomic, and payer status disparities in utilization of unicompartmental knee arthroplasty in the USA - Suraj A. Dhanjani; Jessica Schmerler; Nauman Hussain; Daniel Badin; Uma Srikumaran; Vishal Hegde; Julius K. Oni (Knee Surgery & Related Research)
Abstract Background Unicompartmental knee arthroplasty (UKA) is a surgical treatment for knee osteoarthritis associated with lower morbidity compared with total knee arthroplasty (TKA) in patients with isolated unicompartmental knee arthritis. As disparities have been noted broadly in arthroplasty care, it follows that such disparities might be present in the utilization of UKA relative to TKA. This study therefore examined racial/ethnic, socioeconomic, and payer status differences in utilization of UKA. Methods Patients who underwent UKA or TKA between 2016 and 2020 in the National Inpatient Sample were identified. Multivariable Poisson regression models adjusted for hospital geographic region and patient characteristics [age, sex, and Elixhauser Comorbidity Index (ECI)] were used to examine the effect of race/ethnicity, socioeconomic status, and payer status on incidence rate ratio of UKA relative to TKA. Results Of the 8472 UKA patients and 639,937 TKA patients identified between 2016 and 2020, 8027 (94.7%) UKA patients and 606,028 (94.7%) TKA patients met inclusion criteria. Patients who underwent UKA were significantly younger (63.5 ± 10.7 years) than patients who underwent TKA (66.8 ± 9.5 years; p < 0.001) and had significantly lower ECI scores (1.8 ± 1.5) than patients who underwent TKA (2.2 ± 1.6; p < 0.001). Black patients were less likely to undergo UKA relative to TKA compared with white patients [incidence rate ratio (IRR) 0.64, confidence interval (CI) 0.58–0.71, p < 0.001]. Compared with patients in income quartile 4, patients in income quartiles 1 and 2 underwent UKA at a lower relative rate (IRR 0.85, CI 0.79–0.90, p < 0.001 and IRR 0.87, CI 0.82–0.93, p < 0.001, respectively). Compared with patients with private insurance, patients with Medicare underwent UKA at a lower relative rate (IRR 0.83, CI 0.79–0.88, p < 0.001). Conclusions Black patients, lower-income patients, and Medicare-insured patients undergo UKA at a lower relative rate than white, higher-income, and privately insured patients, respectively. Further research may help elucidate reasons for these differences and identify targets for intervention.